Mably on Esteem, Republicanism, and the Question of Human Corruption - Andreas Blank (Journal of Modern Philosophy)
Gabriel Bonnot de Mably (1709–1785) takes up the republican commonplace that the desire for esteem is what could motivate the fulfilment of duties of civic virtue. This commonplace, however, has become problematic through the discussion of the problem of human corruption in philosophers such as Blaise Pascal (1623–1662) and Nicolas Malebranche (1638–1715). In this article, I will show that Mably takes this problem seriously. However, his critique of Malebranche’s solution to this problem and his critique of the economic reinterpretation of Malebranche’s concept of natural order in the work of Le Mercier de la Rivière (1719–1801) motivate his own republican defense of the moral value of the desire for esteem. What makes this defense plausible is his argument that distorted esteem derives from imagination that is distorted, not only as a result of natural factors, but in many cases rather as a result of misguided politics. If some cases of distorted esteem derive from misguided politics, Mably argues, then they can be modified by republican constitution building that modifies the imagination of citizens.